2020
DOI: 10.1016/j.jhepr.2020.100171
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of sarcopenia and physical inactivity to mortality in people with non-alcoholic fatty liver disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) and sarcopenia have similar pathophysiological profiles. In our study, amongst NAFLD patients, sarcopenia was inversely related to increased physical activity level. The presence of sarcopenia in patients with NAFLD poses increased risk for all-cause and cardiacspecific mortality. Lay summary Nonalcoholic fatty liver disease (NAFLD) and sarcopenia have similar pathophysiological profiles. Our data show that sarcopenia is associated with inactivity in subjects with NAFL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
63
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 41 publications
(49 reference statements)
6
63
0
Order By: Relevance
“…32,33 A recent study analysing the NHANES 1999-2004 dataset reported a close association between sarcopenia-related NAFLD defined using noninvasive panels and mortality consistent with our study. 34 The third NHANES (1988)(1989)(1990)(1991)(1992)(1993)(1994)) is a unique database as it included details of hepatic ultrasonography. Therefore, we utilized this database to add uniform objectivity and improve the accuracy of the definition of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 A recent study analysing the NHANES 1999-2004 dataset reported a close association between sarcopenia-related NAFLD defined using noninvasive panels and mortality consistent with our study. 34 The third NHANES (1988)(1989)(1990)(1991)(1992)(1993)(1994)) is a unique database as it included details of hepatic ultrasonography. Therefore, we utilized this database to add uniform objectivity and improve the accuracy of the definition of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…The strengths of our study included a longer follow-up period (median follow-up 23.2 vs 13.5 years), larger sample size (11 065 vs 4611), and a significantly higher number of outcomes (3342 vs 587 deaths). 34 Although there was substantial follow-up mortality data up to 13.5 years, we hypothesized that a longer follow-up period spanning over 25 years may allow us to establish an independent association of ultrasonographically-defined NAFLD with all-cause and cause-specific mortality based on the natural history of NAFLD characterized by its slow progression. In addition, our study showed that individuals with NAFLD and coexisting sarcopenia were noted to have an increased risk of diabetes-related mortality.…”
Section: Discussionmentioning
confidence: 99%
“…This means that those subjects with high BMI are less likely to be classified as having sarcopenia. Therefore, weight-adjusted or BMI-adjusted sarcopenia indices are more appropriate in patients with nonalcoholic fatty liver disease (NAFLD), which is associated with obesity [18,70,71]. The FNIH definition proposed sex-specific cutoff values of the sarcopenia index, in which the ASM is divided by BMI (men < 0.789 and women < 0.521) [25].…”
Section: Dual Energy X-ray Absorptiometry (Dxa)mentioning
confidence: 99%
“…The FNIH definition proposed sex-specific cutoff values of the sarcopenia index, in which the ASM is divided by BMI (men < 0.789 and women < 0.521) [25]. This cutoff value has mainly been used in research on NAFLD [18,71]. In addition, some researchers defined the lowest quintile of the ASM_BMI as sarcopenia [19], or defined sarcopenia using upper limb muscle mass [68,72].…”
Section: Dual Energy X-ray Absorptiometry (Dxa)mentioning
confidence: 99%
“…Owing to the rapid decline in physical activity of the general population resulting from the global scale lockdown due to the COVID-19 pandemic and prolonged restriction of movement with the resultant increase in telecommuting, there are concerns regarding various components of metabolic syndrome, muscle weakness, and other health problems [5]. Moreover, people who previously engaged in physical activity, including commuting to work, may rapidly develop inactivity-induced fatty liver [6]. However, this cannot be assessed over a short time without continuous measurements.…”
Section: Discussionmentioning
confidence: 99%